Risk of Hypertension in Adolescents with Over Nutritional Status in Pangkalpinang, Indonesia - Mirza Yusrizal; Dono Indarto; Muhammad Akhyar (Masters Program in Public Health, 2016)
Background: Adolescents are the changes of children to be adults. Gender, family history of disease, age, sodium intake and physical activity affect the pravelence of hypertensionAdolescences are the time change from children into adults. Gender, family history of disease, body mass index or BMI according to age, sodium intake and physical activity affect the prevalence of hypertension in adulthood. Hypertension disorders in teenagers most will settle on adulthood. This study aimed to analyze risk factors of hypertension in adolescent aged 15-17 years with over nutritional status.Subject and Methods: This was an observational analytic study with cross sectional design. This was conducted in Pangkalpinang, Bangka Belitung Indonesia. A total of 120 students in grade X-XI in four high schools were selected by fixed-exposure sampling. BMI measurement used antropometri. Physical activity questionnaire used International Physical Activity Questionnaire. Sodium intake was measured with a food frequency questionnaire. Blood pressure was measured by using a sphygmomanometer. Data analysis was using a multiple linear regression.Results: Gender and nutritional status more positively associated with hypertension, (B = 5.77; p = 0.017) and (B = 4.85; p = 0.001), while sodium intake, family disease history and physical activity have a negative relationship, (B = 0.01; p = < 0.076), (B =-1.73; p = 0.481) and (B = >-0.01; p = 0.592). Multiple linear analysis obtained adjusted R2 = 0356 (35.6%).Conclusions: Young men have a higher average blood pressure than women of 5.77 mmHg. Any increase of 1 kg/m2 equivalent BMI will raise the blood pressure of 4.85 mmHg. Adolescents with more nutritional status can increase knowledge about hypertension, as well as regulate eating habits according to needs of physical growth and development.Keywords: hypertension, adolescent, gender, family history of disease, BMI, sodium intake, physical activity.Correspondence: Mirza Yusrizal. Health Department of Pangkalpinang, Bangka Belitung, Indonesia. Email: mirzayusrizal@yahoo.co.idJournal of Epidemiology and Public Health (2016), 1(1): 27-36https://doi.org/10.26911/jepublichealth.2016.01.01.04